O‘SMIRLAR VA YOSH BOLALARGA CHET TILLARINI SAMARALI TEXNOLOGIYALAR ASOSIDA O'RGATISH METODIKASI («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article discusses the prospects for teaching foreign languages to young children and adolescents using effective educational methods and their implementation, as well as methods for learning and teaching foreign languages through highly qualified personnel and technologies.
Keywords: Technology, method, training, children, adolescents, quality, effective education.